5-Aminolevulinic acid combined with sodium ferrous citrate mitigates effects of heat stress on bovine oocyte developmental competence - Omnia ELGENDY; Go KITAHARA; Shin TANIGUCHI; Takeshi OSAWA (The Society for Reproduction and Development, 2022)
High summer temperatures have deleterious effects on oocyte developmental competence. The antioxidant and autophagy-related properties of 5-aminolevulinic acid (5-ALA) gives the compound a broad range of biological activities. This study aimed to evaluate the effects of: 1) a high temperature-humidity index (THI) on the developmental competence of bovine oocytes, and 2) 5-ALA administration in combination with sodium ferrous citrate (SFC) during in vitro maturation (IVM) on bovine oocyte developmental competence evaluated at high THI. Bovine ovaries were collected from a local slaughterhouse at moderate environmental temperature (MT; THI of 56.2) and high environmental temperature (HT; THI of 76.7) periods; cumulus-oocyte complexes (COCs) were aspirated from medium-sized follicles, matured in vitro for 22 h, fertilized, and cultured for 10 days. For COCs collected during the HT period, 0 (control), 0.01, 0.1, 0.5, or 1 µM 5-ALA was added to the maturation medium in combination with SFC at a molar ratio of 1:0.125. The results showed that HT adversely affected blastocyst and hatching rates compared with MT. Adding 5-ALA/SFC (1 µM/0.125 µM) to the maturation medium of oocytes collected during the HT period improved cumulus cell expansion and blastocyst rates compared with the no-addition control. In conclusion, this study showed that high THI can disrupt bovine oocyte developmental competence. Adding 5-ALA to SFC ameliorates this negative effect of heat stress and improves subsequent embryo development.